Fundamentos gnoseológicos del desarrollo de la competencia profesional gestionar proyectos microempresariales (Management Challenges, 2023)
Aim: To provide a cognitive rationale for mini-company project management processes. Methods and techniques: The research methods used were, in essence, analysis and synthesis and induction-deduction.Main results: The outcome was associated with the arrangement of contributions to processes pertaining to professional competency and its assessment,0. depending on the components of the system studied.Conclusions: The rationale for scientific argumentation of a didactic strategy to develop the competence was established.project-based learning, project managing, mini-company
Keywords: project-based learning; project managing; mini-company